Genome-Based Analyses of Fitness Effects and Compensatory Changes Associated with Acquisition of blaCMY-, blaCTX-M-, and blaOXA-48/VIM-1-Containing Plasmids in Escherichia coli - Michael Pietsch (Antibiotics, 2021)
(1) Background: Resistance plasmids are under selective conditions beneficial for the bacterial host, but in the absence of selective pressure, this carriage may cause fitness costs. Compensation of this fitness burden is important to obtain competitive ability under antibiotic-free conditions. In this study, we investigated fitness effects after a conjugative transfer of plasmids containing various beta-lactamase genes transferred into Escherichia coli. (2) Methods: Fourteen beta-lactamase-encoding plasmids were transferred from clinical donor strains to E. coli J53. Growth rates were compared for all transconjugants and the recipient. Selected transconjugants were challenged in long-term growth experiments. Growth rates were assessed at different time points during growth for 500 generations. Whole-genome sequencing (WGS) of initial and evolved transconjugants was determined. Results: Most plasmid acquisitions resulted in growth differences, ranging from −4.5% to 7.2%. Transfer of a single blaCMY-16-carrying plasmid resulted in a growth burden and a growth benefit in independent mating. Long-term growth led to a compensation of fitness burdens and benefits. Analyzing WGS revealed genomic changes caused by Single Nucleotide Polymorphisms (SNPs) and insertion sequences over time. Conclusions: Fitness effects associated with plasmid acquisitions were variable. Potential compensatory mutations identified in transconjugants’ genomes after 500 generations give interesting insights into aspects of plasmid–host adaptations.